Traffic analysis and evaluation for Lindholmsallén: current and 2035 situations - Ntoukolis, Nikolas (My University, 2020)
Traffic-related issues are major concern in cities for their current development and functioning, but also for future development and expansion. The ever-growing population and the economic development combined with constant change of land use brings further traffic and infrastructure issues. The Lindholmen area in Gothenburg is being developed and going through a major land change use. Different studies have been conducted to assess the traffic situation, queue length and travel time in Lindholmsallén and the roads connecting to it. The traffic demand in the area is heavy during peak hours, and normal to light during the rest of a day. The main artery, Lindholsallén, is the entry connection to Lindholmens residential and office/school areas. The land use of Lindholmen is transforming from a semi/industrial – residential area to a fully residential/office space area. The main changes include the new student housing buildings, the new office space besides the Radisson blue hotel and a new luxury skyscraper of the city (i.e., the Karlatornet). The analysis, simulation and predictions are continually used to help with intra-city and inter-city traffic management and improvement. A Vissim model is build and the traffic counted in the area during the peak hours is used as base for simulations of a heavy traffic situation. The future traffic situation is predicted for the year 2035, when almost all the changes in the area will be finished. The main outcome from the simulation and result analysis shows that the area has problems with travel time and queuing. These problems negatively affect the L.O.S and user experience. Lindholmsallén needs a remodelling and intervention since in its main connections with the other systems and some parts within the are itself have queuing problems and longer travel time of users. The same problems but in a more severe matter are seen also in the future scenario simulations. The problems become even more visible since they effect other areas in the future. In order to improve the traffic situation in the area, some measures to improve the current traffic situation are recommended. Dedicated turn lanes and signals in some parts where there are none can help the traffic. While based in the future traffic growth and area development, an intervention in the infrastructure system and construction of new lanes and corridors to lower the traffic flow, together with measure that make the area more accessible through public transport. The measures are focused on making the infrastructure system users experience and the overall traffic situation in the area better, while separating the vehicle mode corridors. This and other solutions are recommended and are also being researched currently by governmental entities.
Keywords: Traffic flow; Travel time; Queueing; Peak hour; Traffic Simulation; Scenarios; Traffic Prediction; Lindholmen; Gothenburg